Atomic Structure Modification for Electrochemical Nitrogen Reduction to Ammonia. Issue 3 (11th December 2019) - Chen, Xinrui; Guo, Yitian; Du, Xinchuan; Zeng, Yushuang; Chu, Junwei; Gong, Chuanhui; Huang, Jianwen; Fan, Cong; Wang, Xianfu; Xiong, Jie
Abstract: The electrochemical nitrogen reduction reaction (NRR), as an environmentally friendly method to convert nitrogen to ammonia at ambient temperature and pressure, has attracted the attention of numerous researchers. However, when compared with industrial production, electrochemical NRR often suffers from unsatisfactory yields and poor Faraday efficiency (FE). Recently, various structure engineering strategies have aimed to introduce extra active sites or enhance intrinsic activity to optimize the activation and hydrogenation of N2 . In this review, recent progress in atomic structure modification is summarized and discussed to design high‐efficiency NRR catalysts, with a focus on defect engineering (heteroatom doping and atom vacancy), surface orientation and amorphization, as well as heterostructure engineering. In addition, existing challenges and future development directions are proposed to obtain more credible NRR catalysts with high catalytic performance and selectivity. Abstract : The recent progress in nitrogen reduction reaction (NRR) electrocatalysts is summarized with a focus on the atomic structure modification including defect engineering, surface orientation and amorphization, as well as heterostructure engineering. Existing challenges and future development directions are also highlighted to obtain more credible NRR catalysts.